Problem Based Learning (PBL) Using Lego in Presenting Data - Lado Bestra; Chika Rahayu; Helni Indrayati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Problem-solving ability in the learning process is needed to practice Skills in finishing problems, especially in learning mathematics related to life every day. The study aims to know the application of the problem-based learning (PBL) model using Lego in the material presentation of data in Class VII SMPN 2 Pagar Alam. The research method was experimental, with design studies of one-shot cases on all categories. The subjects of this study were class VII students of SMPN 2 Pagar Alam. The sample amounted to 32 students. The data analysis used pre and post-test sheets. From the result analysis, the average value of student learning is 90.58. Thereby implementing the PBL model on the material presentation of data for the results study, students rated very well. Besides that, matter interesting when research students are excited about using Lego as a learning media in the classroom.